PREFACE. The 1st Baltic Osseointegration Academy and Lihuanian University of Health Sciences Consensus Conference 9 - 10 September 2016, Kaunas, Lithuania - Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research, 2016)
Baltic Ossoeintegration Academy (BOA) together with the Lithuanian University of Health Sciences (LSMU) and Universities from Europe and USA organized their first Consensus Conference (CC) devoted to the topic of peri-implantitis. BOA - LSMU consensus development group (CDG) was seeking to review the dental literature on a topical area in implantology and to produce high-quality, unbiased evidence-based guidelines and consensus statement (CS). CDG as the responsible body formulated the task of developing CS devoted to the topic of peri-implantitis to Gintaras Juodzbalys (Lithuania). CS Panel members were invited by the chairman. They are representatives of Universities, experts in a field and made every effort to produce nonbiased, independent, evidence-based clinical practice guidelines. Panel members had no conflicts of interest and signed a Panel Member Agreement (PMA). Working groups were established and following clinically relevant topics suitable for consensus discussion were identified: